CATECHOLASE ACTIVITY OF A COPPER(II) COMPLEX WITH THE 2-(5-(1,2,4)TRIAZOLE-1-ILMETHYL-1H-(1,2,4)-TRIAZOLE-3-IL)-PYRIDYL: DOI: https://doi.org/10.17721/1728-2209.2020.1(57).5 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
Methods of the synthesis of 2-(5-(1,2,4)triazol-1-ylmethyl-1H-(1,2,4)-triazol-3-yl)-pyridine and a binuclear copper complex are described. The structure of the complex is established by X-ray structural analysis. The complex is a centrosymmetric [Cu2(L)2(NO3)2·2H2O].H2O dimer. The Cu-Cu distance is 4.0408 (3) Å. In the complex the ligand is in a deprotonated state. Due to this, the triazole fragment acts as a bridge between the two metal centers. Copper ions are in an octahedral environment. The equatorial plane is formed by three triazole nitrogen atoms and one pyridyl nitrogen atom. The axial positions are occupied by a water molecule and a nitrate ion.  Isotropic patterns corresponding to binuclear copper particles of the [Cu2L2-H]+ composition were registered in the ESI mass spectra of the solution of the [Cu2(L)2(NO3)2(H2O)2]·H2O complex. These data confirm the presence of a binuclear complex in solution. The catecholoxidase activity of the binuclear copper (II) complex based on 2-(5-(1,2,4)triazol-1-ylmethyl-1H-(1,2,4)-triazol-3-yl)-pyridine was studied. The kinetics of model reactions of the catecholase type were investigated by the method of initial velocities using a model substrate of 3,5-di-tert-butyl catechol (3,5-DTBK). At low concentrations of 3,5-DTBK, the dependence of the initial oxidation rate on the concentration of the substrate is linear, which corresponds to the first order of the reaction on the substrate. However, the dependence graph at higher concentrations of 3,5-DTBK is nonlinear and indicates the saturation of the catalyst with the substrate. The form of the dependence of the initial reaction rate on the substrate concentration is explained within the framework of the Michaelis-Menten model, which well describes the behavior of natural metaloenzymes.
Keywords: 1,2,4-triazole, copper(II) complexes, X-raycrystallography.